2011
DOI: 10.1021/jp110128t
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosynthesized BiFeO3 Nanoparticles with Highly Reactive Surface and Enhanced Magnetization

Abstract: A one-step synthesis of nanostructured bismuth ferrite (BiFeO3) via mechanochemical processing of a α-Fe2O3/Bi2O3 mixture at room temperature is reported. The mechanically induced phase evolution of the mixture is followed by XRD and 57Fe Mössbauer spectroscopy. It is shown that the mechanosynthesis of the rhombohedrally distorted perovskite BiFeO3 phase is completed after 12 h. Compared to the traditional synthesis route, the mechanochemical process used here represents a one-step, high-yield, low-temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 65 publications
(83 reference statements)
5
77
0
Order By: Relevance
“…The amorphous phase is mostly located on the particle surface (core/shell structure). 177 The presence of a destruction limit in brittle materials is confirmed by Fig. 12.…”
Section: Single-phase Nanosystemsmentioning
confidence: 64%
“…The amorphous phase is mostly located on the particle surface (core/shell structure). 177 The presence of a destruction limit in brittle materials is confirmed by Fig. 12.…”
Section: Single-phase Nanosystemsmentioning
confidence: 64%
“…[13][14][15] Besides activation, mechanochemistry has also successfully been used for the synthesis of a variety of materials from precursors at room temperature including oxides and fluorides. [16][17][18] However, in contrast to such a top-down approach, the preparation of nanostructured particles by precipitation from aqueous solution is much more beneficial when the shape and surface morphology of the crystallites have also to be controlled. By following such a route, the corresponding salts, for example nitrates or oxides, are reacted with hydrofluoric acid and subsequent dehydration is carried out by annealing at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the lattice fringes observed on the crystalline particles showed an interplanar distance of ³4.0 ¡, corresponding with the (012) planes of the perovskite structure and in good agreement with the values reported in literature. 29) The atomic composition of the particles, as estimated from EDS analyses, evidenced a Bi/Fe ratio µ 1. It is worth to mention at this point that these EDS analyses were carried out with relatively short acquisition times, namely around 30 s; this is because, as a consequence of the far-from-equilibrium state of the surface shell in the mechanosynthesized nanoparticles, a prolonged exposure time (above 60 s) unavoidably promotes the crystallization of the particles under the electron beam.…”
Section: Resultsmentioning
confidence: 97%
“…But moreover, all particles seem to be surrounded by an amorphous layer with a width of just a few nanometers; as described in the literature, such morphology is characteristic of mechanosynthesized BiFeO 3 powders. 27), 29) Da Silva et al 29) suggested that the observed amorphous layer is associated with the area where the heterogeneous processes of nucleation and growth of BiFeO 3 crystallites are spatially confined: during high-energy milling the reaction precursors are mixed at the molecular level and the new mechanosynthesized phase nucleates at the interfaces between the solid reactants. On the other hand, the lattice fringes observed on the crystalline particles showed an interplanar distance of ³4.0 ¡, corresponding with the (012) planes of the perovskite structure and in good agreement with the values reported in literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation